Kewenangan Penyelesaian Sengketa Pemilihan Kepala Daerah Pasca Putusan Mahkamah Konstitusi Nomor 85/PUU-XX/2022 - Saragih, Geofani Milthree (Universitas Proklamasi 45, 2022)
Indonesia is a country that upholds people's sovereignty which is carried out based on law, this is confirmed constitutionally in Article 1 paragraph (2) of the 1945 Constitution. In electing leaders, the people are allowed to determine them directly, namely through an election process. At the regional level, there are Regional Head Elections (Pilkada). Initially, the Supreme Court had the authority to resolve regional election disputes as emphasized in Article 106 paragraph (1) of Law Number 32 of 2004 concerning Regional Government. In its development, this authority was transferred to the Constitutional Court with the passing of Law Number 12 of 2008 concerning the Second Amendment to Law Number 32 of 2004 concerning Regional Government. Then, the authority of the Constitutional Court in deciding disputes over regional head election results was declared unconstitutional through Constitutional Court Decision Number 97/PUU-XI/2013. However, in the end, the Constitutional Court again took over the authority to resolve regional election disputes through Constitutional Court Decision Number 85/PUU-XX/2022. In this study, we will discuss the authority to resolve regional election disputes while still at the Supreme Court. Then, the following discussion examines the discourse on forming a particular judicial body in resolving regional election disputes. The final debate will examine the authority to resolve regional election disputes of the Constitutional Court from when it was still a temporary authority until it became a permanent authority after Constitutional Court Decision Number 85/PUU-XX/2022.